How AI Affects Health Equity: Opportunities, Risks, and the Path Forward - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The rapid integration of Artificial Intelligence AI into healthcare promises a revolution in diagnostics, treatment, and patient management. However, as AI s...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine